Creep Damage Evolution of Marble From Acoustic Emission and the Damage Threshold - Liu, Xueying; Yu, Jin; Zhu, Yaoliang; Yao, Wei; Lai, Yongming (Frontiers in Earth Science, 2020)
For the underground engineering, time-dependent behaviour(i.e creep) of rocks is one of the main reasons for instability of surrounding rock in great stress conditions. It is important to investigate more details on time-dependent deformation for understanding the mechanical behaviour of rock over timescales. In the present work, conventional compression tests were performed firstly to study mechanical properties and determine the stress levels for creep tests. Secondly, the creep behaviour of the marble was investigated at the great stress proportion of 80%, 85% and 90% of corresponding peak strength under uniaxial and triaxial compression, combined with Acoustic Emission (AE) technique. Results show that creep curves at the stress ratio of 80% and 85% exhibit three stages of the idealized creep curves, while curves at the stress ratio of 90% exhibit two stages. Damage variables, calculated based on instantaneous cumulative AE energy and total amount, augment slightly initially and increase rapidly subsequently before failure, and the turning points in D-t/tf curves can be observed when t/tf is 0.3, defined as the initial-damage escalation threshold, and D increases moderately when t/tf exceeds 0.85. These results provide a foundation to study creep behaviour and predict creep failure.